2015
DOI: 10.1080/13803395.2015.1010489
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effects of cannabis use and decision making on the relationship between conduct disorder and risky sexual behavior

Abstract: Risky sexual behavior (RSB) is a current public health concern affecting adolescents and young adults. Conduct disorder, cannabis use and decision making (DM) ability are interrelated constructs that are relevant to RSB; however, there is little research on the association of DM and RSB. Participants were 79 cannabis users assessed through self-report measures of RSB and mental health, and a timeline follow-back procedure for substance use. DM ability was assessed via the Iowa Gambling Task. We found that more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 75 publications
0
14
1
Order By: Relevance
“…Currently, the literature on the association between decision-making and RSB have mixed results. First, poorer performance on the IGT has been found to moderate the association between substance use and other psychosocial factors and RSB, such that greater substance use is associated with more RSB (Schuster, Crane, Mermelstein, & Gonzalez, 2012;Ross, Coxe, Schuster, Rojas, & Gonzalez, 2015). Furthermore, Golub and colleagues (2012) reported that among a group of substance dependent adults, those who performed poorly on executive function tasks engaged in the greatest number of high risk sexual behavior and high risk sexual behavior under the influence.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the literature on the association between decision-making and RSB have mixed results. First, poorer performance on the IGT has been found to moderate the association between substance use and other psychosocial factors and RSB, such that greater substance use is associated with more RSB (Schuster, Crane, Mermelstein, & Gonzalez, 2012;Ross, Coxe, Schuster, Rojas, & Gonzalez, 2015). Furthermore, Golub and colleagues (2012) reported that among a group of substance dependent adults, those who performed poorly on executive function tasks engaged in the greatest number of high risk sexual behavior and high risk sexual behavior under the influence.…”
Section: Introductionmentioning
confidence: 99%
“…cannabis, alcohol, tobacco, etc.) across a participant’s lifespan (3941). The Substance Use Disorders Module of the Structured Clinical Interview for DSM-IV Disorders was administered to assess substance abuse and dependence (42).…”
Section: Methodsmentioning
confidence: 99%
“…Cannabis users are more likely to report sexual intercourse without the use of birth control, casual sex and multiple sexual partners than nonusers. [3][4][5][6][7][8] As consequences of these behaviours, cannabis users have a greater risk than nonusers of STDs and unintended pregnancies. 9 Many studies have shown that cannabis abusers tend to exhibit neurocognitive deficits in mechanisms associated with impulsivity, suggesting that cannabis abuse affects brain structures involved in inhibitory control 10 -effects that may persist after many days of abstinence.…”
Section: Introductionmentioning
confidence: 99%